2017
DOI: 10.1051/matecconf/201713702007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of additive technologies in elementary education

Abstract: Abstract. The use of additive manufacturing (AM) in the wider sense at the level of elementary education is not sufficiently analysed in Republic of Croatia at the moment. Partially, CAD/CAM technologies requires far more specialized knowledge than what the Croatian curriculum provides. The application of different technological devices in the educational process, accelerates the teaching process, and makes it more interesting and more acceptable. The knowledge that pupil need to have at the end of schooling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…There are several actions and experiments reported in the literature documenting the advantages of introducing AM into training, both for schools [ 33 , 75 , 76 , 77 , 78 ] and for universities [ 36 , 37 , 39 , 79 ], for teachers [ 38 ], national plans [ 69 , 80 ], and even in libraries [ 35 ]. These experiments have shown that, in addition to the disciplines mentioned inherent to manufacturing, participants also develop other nontechnical skills such as teamwork and collaboration, creativity, flexibility vis-à-vis changes, communication skills, handling of changing information, concentration, planning, perseverance, and self-control.…”
Section: Implications For Education and Design Of Training Programmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several actions and experiments reported in the literature documenting the advantages of introducing AM into training, both for schools [ 33 , 75 , 76 , 77 , 78 ] and for universities [ 36 , 37 , 39 , 79 ], for teachers [ 38 ], national plans [ 69 , 80 ], and even in libraries [ 35 ]. These experiments have shown that, in addition to the disciplines mentioned inherent to manufacturing, participants also develop other nontechnical skills such as teamwork and collaboration, creativity, flexibility vis-à-vis changes, communication skills, handling of changing information, concentration, planning, perseverance, and self-control.…”
Section: Implications For Education and Design Of Training Programmentioning
confidence: 99%
“…The strengths of AM and the challenges—not only technical—to be overcome are classified. The need for competent personnel with specific skills and know-how within this timeframe and the track record of experiments performed regarding teaching combined with AM [ 5 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] enable the advantages of including AM in syllabuses to be set out from primary education through to university-level courses.…”
Section: Introductionmentioning
confidence: 99%